Bolometric light curves and explosion parameters of 38 stripped-envelope core-collapse supernovae. Issue 1 (20th January 2016) - Lyman, J. D.; Bersier, D.; James, P. A.; Mazzali, P. A.; Eldridge, J. J.; Fraser, M.; Pian, E.
Abstract: Literature data are collated for 38 stripped-envelope core-collapse supernovae (SE SNe; i.e. SNe IIb, Ib, Ic and Ic-BL) that have good light-curve coverage in more than one optical band. Using bolometric corrections derived in previous work, the bolometric light curve of each SN is recovered and template bolometric light curves provided. Peak light distributions and decay rates are investigated; SNe subtypes are not cleanly distinguished in this parameter space, although some grouping of types does occur and there is a suggestion of a Phillips-like relation for most SNe Ic-BL. The bolometric light curves are modelled with a simple analytical prescription and compared to results from more detailed modelling. Distributions of the explosion parameters show the extreme nature of SNe Ic-BL in terms of their 56 Ni mass and the kinetic energy, however ejected masses are similar to other subtypes. SNe Ib and Ic have very similar distributions of explosion parameters, indicating a similarity in progenitors. SNe IIb are the most homogeneous subtype and have the lowest average values for 56 Ni mass, ejected mass, and kinetic energy. Ejecta masses for each subtype and SE SNe as a whole are inconsistent with those expected from very massive stars. The majority of the ejecta mass distribution is well described by more moderately massive progenitors in binaries, indicating these are the dominant progenitor channel for SE SNe.